2017
DOI: 10.1038/srep44283
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Campylobacter jejuni infection in the gnotobiotic piglet and genome-wide identification of bacterial factors required for infection

Abstract: To investigate how Campylobacter jejuni causes the clinical symptoms of diarrhoeal disease in humans, use of a relevant animal model is essential. Such a model should mimic the human disease closely in terms of host physiology, incubation period before onset of disease, clinical signs and a comparable outcome of disease. In this study, we used a gnotobiotic piglet model to study determinants of pathogenicity of C. jejuni. In this model, C. jejuni successfully established infection and piglets developed an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Genome sequencing of numerous strains has revealed genomic flexibility in C. jejuni and C. coli and has indicated possible host-specific genotypes but has not yet identified possible virulence determinants (Van Putten et al 2009 ; Yahara et al 2017 ). Similarly, genome-wide functional screening (using mutant panels) is beginning to provide evidence for fitness, colonisation and virulence determinants besides flagella and glycosylation systems (de Vries et al 2017a , b ). To date, C. jejuni has been subject to metabolomics studies where novel glycosylation events of flagella were observed (McNally et al 2007 , 2006 ; Logan et al 2009 ), resistance to antibiotic (Li et al 2015 ), metabolic mutant differentiation (Howlett et al 2014 ), and preferential utilisation of amino acids was shown through NMR analysis of depletion from complex growth medium (Wright et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genome sequencing of numerous strains has revealed genomic flexibility in C. jejuni and C. coli and has indicated possible host-specific genotypes but has not yet identified possible virulence determinants (Van Putten et al 2009 ; Yahara et al 2017 ). Similarly, genome-wide functional screening (using mutant panels) is beginning to provide evidence for fitness, colonisation and virulence determinants besides flagella and glycosylation systems (de Vries et al 2017a , b ). To date, C. jejuni has been subject to metabolomics studies where novel glycosylation events of flagella were observed (McNally et al 2007 , 2006 ; Logan et al 2009 ), resistance to antibiotic (Li et al 2015 ), metabolic mutant differentiation (Howlett et al 2014 ), and preferential utilisation of amino acids was shown through NMR analysis of depletion from complex growth medium (Wright et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Induction of formate dehydrogenase is observed when C. jejuni is grown in a rabbit ileal‐loop ex vivo (Stintzi et al ., ), but not during chicken colonization (Woodall et al ., ; Taveirne et al ., ). Moreover, formate utilization is crucial for piglet colonization (Vries et al ., ), efficient colonization of chickens (Weerakoon et al ., ) and pathology in mouse models (Bereswill et al ., ; Kassem et al ., ). Formate also acts as invasion signal for the pathogenic bacterium Salmonella enterica serovar Enteritidis (Van Immerseel et al ., ; Huang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter infection is one of the main bacterial causes of diarrhea and of ‘environmental enteropathy’ and body growth failure. Campylobacter species like Campylobacter jejuni and Campylobacter concisus could cause human diarrhea diseases which originate from piglets via consumption of contaminated meat products ( de Vries et al., 2017 ; Rosner et al., 2017 ). Also, PCV2 infection is widespread in swine industry ( BarĂł et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%